Analisis Penerapan Pembelajaran Berbasis Moderasi Beragama Dalam Membentuk Paham Inklusif Santri - Ahmad Sukran (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
AbstractThis study aims to analyze the implementation of religious moderation-based learning in shaping inclusive understanding among students at SMA Ali Maksum Krapyak Yogyakarta. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that teachers consistently integrate values of moderation such as tawassuth (moderation), tasamuh (tolerance), and i’tidal (justice) into the learning process, particularly in Islamic Religious Education and History subjects. The teaching methods are dialogical and contextual, creating an inclusive learning environment that embraces cultural diversity. Social interactions between teachers and students reflect an affirming and validating atmosphere toward diverse cultural backgrounds. Students’ responses indicate an internalization of moderation values, resulting in attitudinal changes toward greater openness and tolerance. The main supporting factors stem from the school culture and collaborative pesantren environment, while challenges arise from uncontrolled digital information flows and exclusive religious understandings brought by some students. This study confirms that religious moderation-based learning is effective in shaping an inclusive, tolerant, and socially adaptive generation of students in a religiously diverse society